2011
DOI: 10.3109/17435390.2011.620718
|View full text |Cite
|
Sign up to set email alerts
|

Independent cytotoxic and inflammatory responses to zinc oxide nanoparticles in human monocytes and macrophages

Abstract: Significant public and scientific concerns remain for the use of nanoparticles (NPs) in commercial products, particularly those applied topically for skin care. There are currently a range of metal oxides formulated into many sunscreens that are present at the nanoscale. In this study, we sought to determine the effect of the size and dispersion of one type of these NPs (zinc oxide) on immune cell function and cytotoxicity for human macrophages and monocytes, which are key cells for particle and debris clearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
52
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 28 publications
11
52
0
1
Order By: Relevance
“…ZnO NP-induced cytotoxicity could be affected by the release of Zn 2+ ions through the dissolution of ZnO NPs within aqueous culture media. [33][34][35] In terms of EC 50 , we found that ZnO NPs would cause cytotoxicity at lower doses ( 19,36,37 Further, the dose-dependent decrease in cell viability by exposure with ZnO NPs might be related to the dissolution and release of Zn 2+ ions, as previously observed in in-vitro studies. [33][34][35][38][39][40] This Zn 2+ ion would affect cellular differentiation and cellular metabolism solely or via the interaction with proteins in vitro and in vivo.…”
Section: Notessupporting
confidence: 73%
“…ZnO NP-induced cytotoxicity could be affected by the release of Zn 2+ ions through the dissolution of ZnO NPs within aqueous culture media. [33][34][35] In terms of EC 50 , we found that ZnO NPs would cause cytotoxicity at lower doses ( 19,36,37 Further, the dose-dependent decrease in cell viability by exposure with ZnO NPs might be related to the dissolution and release of Zn 2+ ions, as previously observed in in-vitro studies. [33][34][35][38][39][40] This Zn 2+ ion would affect cellular differentiation and cellular metabolism solely or via the interaction with proteins in vitro and in vivo.…”
Section: Notessupporting
confidence: 73%
“…Many studies have shown that the cytotoxicity of nanomaterials depends on their size. 15,[25][26][27] Our study showed similar results. Compared to ZnO a NP treatment, we found a larger number of significant toxic effects following ZnO b NP treatment.…”
supporting
confidence: 81%
“…In this study, we explored the toxicological effects of ZnO NPs using two types of ZnO NPs with various sizes. Many studies have indicated that the physicochemical properties of nanomaterials, including size, 15,[25][26][27] shape, [28][29][30] surface area, 31 ζ-potential, 27,32 and composition, greatly affect their toxicological effects. 23 The results of our study indicated that the ZnO a NPs and ZnO b NPs were rod-shaped with a low aspect ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these responses suggest the charged surface of zinc nanoparticles elicit both dramatic and systemic immunosuppression, which correlated to the observed cytotoxicity in the same cells. The effect of nanoparticle size on immune cell cytotoxicity was evaluated, and similar to prior efforts, [81][82][83] it was reported that smaller particles exhibited a slightly higher EC 50 than smaller zinc oxide nanoparticles The size of the nanoparticle also correlated to cytokine concentration in the serum; the serum levels of pro-inflammatory cytokines were reduced with increased particle size. 84 Another common metal-oxide nanoparticle, titanium oxide, are constituents of many cosmetic and commercial colorants, included in products such as paints and plastics.…”
Section: Metal-oxide Nanoparticlesmentioning
confidence: 97%